Real-World Use of Ruxolitinib Cream: Safety Analysis at 1 Year - Hu, Wilson; Thornton, Michele; Livingston, Robert A. (American journal of clinical dermatology, 2024)
Background Ruxolitinib cream is the first topical Janus kinase (JAK) inhibitor approved in the United States (US) for the treatment of mild to moderate atopic dermatitis and nonsegmental vitiligo. A postmarketing study with oral tofacitinib, approved for rheumatoid arthritis, triggered class warnings for JAK inhibitors, including risk of serious infections, mortality, malignancy, major adverse cardiovascular events, and thrombosis. Because ruxolitinib cream is indicated for inflammatory conditions, it is subject to the same warnings as oral JAK inhibitors in the US. Here, nearly 14,000 patient-years of postmarketing safety data from the first year following market approval of ruxolitinib cream were reviewed. Methods The Incyte global safety database (21 September 2021–20 September 2022) and US FDA Adverse Event Reporting System (as of 30 September 2022) were queried for adverse event (AE) reports received for ruxolitinib cream. Results The search identified 294 postmarketing individual case safety reports containing 589 events, including four serious AEs and no fatal AEs. AEs (i.e., any unfavorable sign, symptom, or disease) representing >2% of all events included application site pain ( n = 16), atopic dermatitis ( n = 15), skin irritation ( n = 15), scratch ( n = 14), and condition aggravated ( n = 13). The four serious AEs were skin cancer ( n = 2), pericarditis, and thrombocytopenia (both n = 1), none of which had sufficient information to assess possible relatedness to ruxolitinib cream. Serious AEs associated with the class warnings for JAK inhibitors were not reported. Conclusions Postmarketing safety data from the year following approval suggest ruxolitinib cream is generally well tolerated, without significant systemic AEs, and with a low incidence of application site reactions.